Size Reduction Method for Laboratory Testing in Hot Mix Asphalt - Jiménez Acuña, Monica (2025)
In 2004 there were not available standardized methods of reducing a large sample of hot mix asphalt and the quartering methods for aggregates were taken as reference, but these do not take into account the temperature at which the mix should be heated to ensure workability and the way to not affect the properties of the mixture within other details. It is for this reason that LanammeUCR implemented a completely new method to be able to certify the sampling of hot mix asphalt in the truck transports, so this study was used to include the quartering method to show that the sub-samples are representative of the lot. An experimental design was developed which included the new quartering method for multiple sampling boxes and then measure the asphalt content and gradation with the ignition test for each subsample and also the maximum theoretical specific gravity was performed, it was shown that with this method it is possible to obtain representative subsamples with good repeatability and also found that the segregation of the mixture was eliminated using the gutter system that in one step the desired subsamples are obtained. This method has 11 years of implementation and the advantages over the standard method AASHTO R 47, published in 2008, is that in this approach the care that must be taken when handling hot mix asphalt are detailed, such as the temperatures at which the sample must be heated and the heating times are established as this significantly affects the material properties. Besides the use of simple hand tools that are easy and economical to manufacture they take into account an ergonomic criteria to ensure that the procedure was safe and practical.